A study to establish the relation of antibiotics and steroids in fungal growth occurring in CSOM patients - Dhingra, Rachna; Monga, Shamim; Kaur, Gurpreet; Kaur, Manpreet; ., Manpreet; Aggarwal, Varun; Singh, Gurpal (International Journal of Advances in Medicine, 2017)
Background: Otitis media is known to be one of most common childhood infections and a leading reason for antibiotic prescriptions in the developed world. Fungal infections superimposed over chronic suppurative. Otitis media is suspected when the discharging ear does not respond to local antibiotic ear drops. The aim of the study is to analyze the relation of antibiotics and steroids in fungal growth occurring in CSOM patients. Methods: Total 150 cases were selected from OPD of ENT department, Government Medical College, Rajindra Hospital, Patiala and divided under two groups: Control group and study group. Results: The antibiotic drop apart from moist and alkaline medium of discharge appears to be mainly responsible for fungal growth and when steroids are added the fungal growth incidence is increased. Thus local drops should be used with great care in treating chronic suppurative otitis media. Conclusions: Local drops with some anti-fungal agents may be the ideal treatment in chronic suppurative otitis media.